Using Technology and Constituting Structures: A Practice Lens for Studying Technology in Organizations - Orlikowski, Wanda J. (Organization Science, 2000)
As both technologies and organizations undergo dramatic changes in form and function, organizational researchers are increasingly turning to concepts of innovation, emergence, and improvisation to help explain the new ways of organizing and using technology evident in practice. With a similar intent, I propose an extension to the structurational perspective on technology that develops a practice lens to examine how people, as they interact with a technology in their ongoing practices, enact structures which shape their emergent and situated use of that technology. Viewing the use of technology as a process of enactment enables a deeper understanding of the constitutive role of social practices in the ongoing use and change of technologies in the workplace. After developing this lens, I offer an example of its use in research, and then suggest some implications for the study of technology in organizations.